Benign metastasizing leiomyoma in triple location: lungs, parametria and appendix - Raś, Renata; Książek, Mariusz; Barnaś, Edyta; Skręt-Magierło, Joanna; Kąziołka, Wojciech; Fudali, Ludmiła; Filipowska, Justyna; Skręt, Andrzej (Menopause Review/Przegląd Menopauzalny, 2016)
Benign metastasizing leiomyoma (BML) usually are situated in one organ, most often in lungs. BML patients typically have a history of uterine leiomyoma treated with hysterectomy, myomectomy or subtotal hysterectomy. The aim of the study was to present the case of a 53-year-old woman with triple location in the lungs, parametria and appendix. She had undergone a myomectomy 26 years earlier. In 2015, she was admitted to the surgical department because of abdominal pain, whereupon a cholecystectomy was performed. CT scans showed pelvic mass with pulmonary metastasis. Upon discharge the patient was referred to the Gynecology Clinic, where a laparotomy was performed. The intraoperative findings were: 1) uterus with multiple leiomyomas, 2) four tumors in the parametria, 3) tumor connected to the appendix. A subtotal hysterectomy, with a bilateral salpingo-oophorectomy, removal of the tumors from the parametria and appendectomy was performed. Pathology confirmed the diagnosis based on morphology and immunohistochemical staining (strongly positive for estrogen receptors and SMA, while Ki67 was very low, below 1%). Upon postoperative recovery, the patient was referred to the Thoracic Surgery Department. During the thoracotomy, multiple nodes, surrounded by lung parenchyma, were revealed. Wedge resection was performed, for localized pulmonary lesions, and sent for pathological examination. The final pathological diagnosis was benign metastasizing leiomyomatosis. In conclusion, the triple location of BML could possibly be a result of a parallel different metastasizing mechanism, although it is impossible to exclude one mechanism, which may be the cause of the metastases in three locations.